Analisis Pengaruh Rate dari Penetapan Harga Lelang Objek Jaminan Gadai di PT Pegadaian Syariah Banda Aceh terhadap Kepuasan Nasabah Debitur - Havna Havna; Syamira Balqis; Muhammad Fitrah Insani (STIKes Ibnu Sina Ajibarang, 2025)
The role of financial institutions in providing access to capital through pawn services is crucial, even though customers face the risk of defaulting, which can lead to the auction of pledged collateral. This study aims to analyze the impact of the auction pricing of collateral at PT Pegadaian Syariah Banda Aceh on customer satisfaction. In this context, a deep understanding of the factors influencing auction pricing and its impact on customer satisfaction is essential to maintain a mutually beneficial relationship. The pricing of the auction is influenced by several factors, including market mechanisms, government regulations, and the company's internal policies. Customer dissatisfaction with auction prices that are perceived as unfair can damage the long-term relationship with the financial institution. Therefore, it is crucial to enhance transparency and fairness in the auction pricing process. Additionally, educating customers about their rights is necessary to provide them with a better understanding of the process and its implications. These measures will help strengthen customer trust and maintain the sustainability of a positive relationship between the financial institution and its customers.